2005
DOI: 10.1088/0953-8984/17/37/011
|View full text |Cite
|
Sign up to set email alerts
|

The full potential Korringa–Kohn–Rostoker method and its application in electric field gradient calculations

Abstract: We have developed a full potential Korringa–Kohn–Rostoker (KKR) Green function method. Three improvements which make the full potential treatment efficient and practical are reported. One is a method for constructing the Green function which satisfies the Wronskian relation exactly. The second is including the contribution of the non-spherical part of the potential in the wavefunctions correctly by use of a modified recursive integral equation. Thirdly, we propose a method that completely eliminates the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…The algebra that leads to Eqs. (29) and (30) is similar to an argument that was put forward previously, 17,18 but, so far as we know, it was never used in the way that we have described.…”
Section: Theorysupporting
confidence: 68%
“…The algebra that leads to Eqs. (29) and (30) is similar to an argument that was put forward previously, 17,18 but, so far as we know, it was never used in the way that we have described.…”
Section: Theorysupporting
confidence: 68%
“…In order to deal with these problems a number of groups developed a full potential (FP) KKR-GF method, obtaining very good results, comparable with full-potential LAPW method (FLAPW), for what concerns total energy calculations, lattice forces, relaxation around an impurity, ( [6,7,8,9,10] and Refs. therein).…”
Section: Introductionmentioning
confidence: 99%
“…( [6,7,8,9,10] and Refs. therein) The only remaining drawback was and is the truncation of the potential at the cell boundary which is still performed via a shape function expanded in spherical harmonics.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, for ordered compounds computations were performed with the full-potential (FP) code, based on the FP-KKR formalism, widely discussed by many authors [40], with technical details shown e.g. when applying to Si [41], or to the electric field gradient calculations [42]. In our practice extracting bands was done with the novel quasi-linear algorithm [43], which allows for more precise and less time-consuming band structure calculations, comparing to conventional techniques.…”
Section: Calculationsmentioning
confidence: 99%